In vitro anti-aging activities of Terminalia chebula gall extract - Manosroi A. (2014)
Context: The Thai Lanna region has its own folklores and wisdoms in various fields such as traditional medicines. The galls of Terminalia chebula Retz. (Combretaceae) frequently appear in many Thai Lanna medicinal plant recipes for promoting longevity. Objectives: To investigate the in vitro anti-aging activities of the extracts from 15 plants including T. chebula gall selected from the Thai medicinal plant recipes that have been traditionally used for longevity. Materials and methods: The plant extracts were prepared by four extraction methods including hot (HW) and cold (CW) aqueous processes and hot (HM) and cold (CM) methanol processes. These extracts were tested for antioxidative and tyrosinase inhibition activity as well as the proliferative and MMP-2 inhibition activity on early aging human skin fibroblasts in order to evaluate their in vitro anti-aging activity. Results: At 0.1mg/mL, the CW extract of T. chebula gall exhibited the highest DPPH radical scavenging activity with scavenging of 84.64%±2.22%, whereas ascorbic acid, α-tocopherol and butylated hydroxyl toluene gave 96.50%±0.1%, 35.74%±0.2% and 27.43%±0.1%, respectively. The CW extract of T. chebula gall indicated the highest stimulation index (SI) on normal human fibroblast proliferation of 1.441 which was more active than ascorbic acid (SI 1.21). This extract has also demonstrated MMP-2 inhibition on fibroblasts determined by zymography 1.37 times more potent than ascorbic acid. Discussion and conclusion: This study has confirmed the traditional use of T. chebula gall in many Thai medicinal plant recipes for longevity which will be beneficial for further development of anti-aging products.